Estrutura, dinâmica e diversidade em um fragmento de floresta de galeria em Itutinga (MG) em um intervalo de dezoito anos - Mariana Piacesi Batista Chaves (2014)
Studies on the spatial and temporal variations of tropical forests have received an increased attention, and results obtained so far in South-eastern Brazil reinforce the need of additional studies. The general purpose of this dissertation was to analyse the changes that took place on the structure, dynamics and species diversity of the tree community of a fragment of gallery forest situated in Itutinga, Minas Gerais state, as well as the existence of spatial patterns and relations with environmental variables regarding topography, soil fertility and water availability, and edge-effects. In 1992, two perpendicular transects were established in order to sample the riparian and interfluvial sectors of the forest fragment, and were made up of 42 adjacent and permanent plots of 15 × 15 m of dimension, Individual trees whose diameter at the ground level was equal to or higher than 5 cm were then measured and identified. The surveys were repeated in 1998, 2005 and 2010, though the minimum size criterion was changed in the last interval to diameter at breast height (dbh, 1,3 m from the ground). For all analyses, only individual that met the latter criterion were considered, after transforming DAP values prior to 2005. Significant changes of the descriptors of tree community structure, dynamics and species diversity indicated forest instability throughout the study period. An overall process of self-thinning, together with the changes in abundance for many species and proportions of functional groups, provided strong evidence that there was a prevailing process of transition toward a more mature stage, although disturbance events interfered locally in a regressive manner, so that the overall process was spatially heterogeneous. The picture was coherent with a likely process of primary succession involving an advance of the forest over the adjacent grasslands. The rates of dynamics were accelerated compared to other forests free of human interference in Southeast of Brazil. The species diversity dropped along the period, particularly in the riparian sector, but this could not be related to the fragments geographic isolation, though a connection with the succession process is quite plausible. The floristic structure was spatially auto-correlated and also related to soil fertility and water availability. The dynamics and diversity, instead, were not significantly related to the environment, so that the history of natural disturbances outstood as the main candidate to explain the observed temporal and spatial variations, giving rise to heterogeneity among plots of the same forest sector. All measures of species diversity showed significant spatial structure; the dynamics rates, instead, showed both random and spatially structured patterns, suggesting that their determining events took place in the forest in both manners. In order to test, in the future, the hypotheses of a significant role of natural disturbances, it will be necessary to start recording both the light incidence in the forest understory and the location and size of the appearing tree-fall gaps.